PRECLINICAL ALTERATIONS OF ORAL EPITHELIAL CELLS IN CONTACT WITH ORTHODONTIC APPLIANCES - de Arruda, Elcy Pinto; Trevilatto, Paula Cristina; Camargo, Elisa Souza; Woyceichoski, Iverson Ernani Cogo; Naval Machado, Maria Angela; Vieira, Iran; de Lima, Antonio Adilson Soares (Biomedical papers, 2011)
Aim: This study evaluated the behavior of oral epithelial cells in contact with orthodontic appliances.Methods: Oral epithelial cells of clinically normal buccal mucosa were obtained by liquid-based exfoliative cytology from 22 orthodontic patients. The following regions were evaluated: a) oral mucosa exposed to friction from orthodontic brackets; b) oral mucosa exposed to friction from the tube on the orthodontic band, and c) oral mucosa not exposed to friction (control area). Nuclear (NA) and cytoplasmic (CA) areas and NA/CA ratio were assessed by an image analysis system. Cell morphology and cellularity were also analyzed by Papanicolaou technique.Results: The NA of the cells in contact with orthodontic brackets and bands were smaller than the control area. Cells in contact with the brackets showed the greatest reduction in CA in comparison with the cells subjected to friction from the tube, and the control group. Smears classified as type I predominated in all regions analyzed, although type II were predominant, together with superficial epithelial cells, mainly in the oral mucosa in contact with the band tube.Conclusion: Preclinical alterations in the epithelial cells of oral mucosa, caused by orthodontic appliances, are reduction in NA, increase in cell keratinization and inflammatory features, especially in the band tube area.
Keywords: Oral epithelium/Exfoliative cytology/Brackets/Orthodontic band/ Orthodontic appliance